Severe mitral stenosis as a cause of paradoxical low-flow, low-gradient severe aortic stenosis: an explorative study on hemodynamics and outcomes - Mohty, Dania; Omer, Mohamed H.; Marek, Josef; Ahmad, Omar; Alhemayed, Waleed; Janjua, Mohamad F.; Capoulade, Romain; Alhumaid, Mohammed; Alassas, Khadija; Sergani, Hani; Pibarot, Philippe; Fadel, Bahaa M. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAortic stenosis (AS) and mitral stenosis (MS) are valvular heart diseases that may present concomitantly, particularly in regions where rheumatic heart disease remains prevalent. While each condition has been extensively studied in isolation, there is limited data on the clinical characteristics of patients with combined AS-MS.MethodsWe retrospectively identified patients with significant AS and concomitant significant MS from the echocardiography database between 2003 and 2018. Exclusion criteria included left ventricular ejection fraction <50%, other significant valvular lesions, prior cardiac surgery, and associated congenital heart disease. Patients with isolated AS were compared to patients with combined AS-MS.ResultsOf 1470 patients with severe AS, a total of 353 patients were included: 41 with combined AS-MS and 312 with isolated AS. The prevalence of combined AS-MS was 11% among patients with significant AS. Compared to patients with isolated AS, patients with combined AS-MS were significantly younger (50 vs. 63 years, p < 0.001), had a lower prevalence of hypertension (44% vs. 64%, P = 0.017) and diabetes (22% v. 42%, p = 0.013), and a greater prevalence of atrial fibrillation (17% vs. 5%, p = 0.003). Patients with combined AS-MS had a significantly larger left atrial size (4.79 ± 0.70 cm vs. 3.93 ± 0.73 cm, p < 0.001), higher peak tricuspid velocities (3.14 ± 0.59 m/s vs. 2.72 ± 0.45 m/s, p < 0.001), and greater prevalence of moderate or severe tricuspid regurgitation (15% vs. 1%, p < 0.001). Echocardiographic parameters assessing transvalvular flow rate did not differ significantly between the two groups. After multivariate adjustment for age and gender combined AS-MS was associated with worse 5-year overall survival (HR 2.672, 95% CI 1.060–6.732, p = 0.037).ConclusionCombined mitral and aortic stenosis is not uncommon (11%) but linked to worse outcomes than isolated AS. Despite expectations, concomitant significant MS did not increase prevalence of paradoxical low-flow, low-gradient AS.